O regime jurídico e fiscal dos fundos de Investimento imobiliário em Angola - Galamba, Emanuel de Oliveira (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2018)
The Angolan state recently decided to reform the legal framework governing real estate investment funds (REIF), which had existed since 2008. The purpose was to create a modern and sophisticated legal and tax regime, with a view to attract investment and thereby creating an effective capital market in the real estate sector. In this context, the purpose of the article is to analyse, in its different dimensions, the legal and tax regime of the REIF, as independent entities without legal status, in the Angolan jurisdiction, including references to its legal nature, types, establishment process and relevant documents, operational rules, assets evaluation, organizational structure, civil liability of the involved entities, rules of advertising and information and to the applicable tax regime. Some final reflections on the REIF’s implementation, short-term and structural difficulties felt since its approval and proposals of amendment of the current regime will be made.